Entropy production estimates for the polyatomic ellipsoidal BGK model. (August 2016) - Park, Sa Jun; Yun, Seok-Bae
Abstract: We study the entropy production estimate for the polyatomic ellipsoidal BGK model, which is a relaxation type kinetic model describing the time evolution of polyatomic particle systems. An interesting dichotomy is observed between 0 < θ ≤ 1 and θ = 0 : In each case, distinct target Maxwellians should be chosen to estimate the entropy production functional from below by the relative entropy. The time asymptotic equilibrium state toward which the distribution function stabilizes bifurcates accordingly.